Primary Politics : How Presidential Candidates Have Shaped the Modern Nominating System - Kamarck, Elaine C. (Book collections on Project MUSE., 2009)
The 2008 presidential primaries produced more drama than many general election campaigns. John McCain overcame the near-implosion of his campaign to capture the Republican nomination by March, despite a strong challenge from quotable pastor-turned-governor Mike Huckabee. Hillary Clinton entered the Democratic race as the heavy favorite, only to fall to a first-term senator from Illinois in a battle that lasted into July. Democratic delegations from Florida and Michigan were unseated and reseated; superdelegates took to the airwaves; and millions of Americans heard of the?robot rule? for the fi.